Estudo da relaxação de "Cole-Cole" em função da frequência e da temperatura em dielétricos lineares - Oliveira, Rinaldo e Silva de (2006)
The Cole-Cole relaxation is used in the description of many systems like dielectric relaxation. The description is done usually empirically demonstrated equation, the dielectric function equation. In this work we did a semi-empiric demonstration of the dielectric function relaxation, through the Kramers-Kroning relations and a study of the time of relaxation distribution function. We propose the use of an electrical circuit to describe the Cole-Cole relaxation, where we have real elements, leading to a better comprehension of the distribution function and Cole-Cole relaxation function. This circuit was used in the study of the capacitive relaxation of a biopolymer (chitosan). In this work we describe new procedure to obtain the dielectric function of frequency and temperature. This technique was used in the study of the dielectric relaxation of a biopolymer (chitosan) and ceramic (CaCu3Ti4O12) as a function of frequency and temperature.